No-Show Rates for Telemedicine Versus In-Person Appointments During the COVID-19 Pandemic: Implications for Medicaid Populations. Issue 4 (October 2022) - Alishahi, Musheng L.; Sevick, Carter; Mathieu, Susan; Everhart, Rachel; Gritz, Mark
Abstract : The objective of this study was to assess no-show rates among in-person and telemedicine visits during the COVID-19 pandemic among Medicaid members. We analyzed data from an urban safety net hospital in Denver, Colorado. Using multivariable binomial regression models, we estimated differences in probability of no shows by patient characteristics and assessed for effect modification by telemedicine use. Overall, the no-show rate was 20.5% with increased probability of no show among Hispanic (2.3%) and non-Hispanic, Black (7.4%) patients compared with their non-Hispanic, White counterparts. Modification by telemedicine was observed, decreasing no-show rates among both groups ( P < .0001). Similar patterns were observed among medically complex patients. Audio-only telemedicine significantly impacted no-show rates within certain populations.